Organic Matter Regulates Ammonia-Oxidizing Bacterial and Archaeal Communities in the Surface Sediments of Ctenopharyngodon idellus Aquaculture Ponds - Dai, Lili; Liu, Chengqing; Yu, Liqin; Song, Chaofeng; Peng, Liang; Li, Xiaoli; Tao, Ling; Li, Gu (Frontiers in Microbiology, 2018)
Ammonia-oxidizing bacteria (AOB) and archaea (AOA) play important roles in nitrogen removal in aquaculture ponds, but their distribution and the environmental factors that drive their distribution are largely unknown. In this study, we collected surface sediment samples from Ctenopharyngodon idellus ponds in three different areas in China that practice aquaculture. The community structure of AOB and AOA and physicochemical characteristics in the ponds were investigated. The results showed that AOA were more abundant than AOB in all sampling ponds except one, but sediment AOB and AOA numbers varied greatly between ponds. Correlation analyses indicated a significant correlation between the abundance of AOB and arylsulfatase, as well as the abundance of AOA and total nitrogen (TN) and arylsulfatase. In addition, AOB/AOA ratio was found to be significantly correlated with the microbial biomass carbon. AOB were grouped into seven clusters affiliated to Nitrosospira and Nitrosomonas, and AOA were grouped into six clusters affiliated to Nitrososphaera, Nitrososphaera sister group, and Nitrosopumilus. AOB/AOA diversity in the surface sediments of aquaculture ponds varied according to the levels of total organic carbon (TOC), and AOB and AOA diversity was significantly correlated with arylsulfatase and β-glucosidase, respectively. The compositions of the AOB communities were also found to be significantly influenced by sediment eutrophic status (TOC and TN levels), and pH. In addition, concentrations of acid phosphatase and arylsulfatase in surface sediments were significantly correlated with the prominent bacterial amoA genotypes, and concentrations of TOC and urease were found to be significantly correlated with the prominent archaeal amoA genotype compositions. Taken together, our results indicated that AOB and AOA communities in the surface sediments of Ctenopharyngodon idellus aquaculture ponds are regulated by organic matter and its availability to the microorganisms.